Japanese Economy: Two Lost Decades and How Many More? - Yoshiyasu Ono (Intereconomics, 2019)
By introducing wealth preference to a dynamic macroeconomic model, instead of those market distortions, we can deal with the secular deficiency of aggregate demand and a discrepancy between fl ow and stock variables.
Keywords: 330